Effects of Serious Games and game-based learning on learners' achievement emotions - Schorer, Antonia; Protopsaltis, Aristidis (Proceedings of the 14th European Conference on Game Based Learning ECGBL 2020, 2020)
The development of new skills and knowledge often leads to challenges. The emotional experience of the learner while confronted with the learning object is crucial for the learning process. Learners who approach a subject with interest and curiosity, and thus value the learning activity with positive emotions, achieve a more promising effect than people who perceive the content as boring, challenging and frightening. Providing positive learning experiences, is the main focus of serious games. Emotional experience, in relation to achievement activities in serious games, are not comprehensively addressed in the scientific debate (Pekrun, 2006; Loderer et al, 2019). In some, approaches which are conceptually closely linked to the perspectives of achievement emotion, for instance in terms of self-efficacy (Ketelhut, 2007; Meluso et al, 2012), are taken into account. The perceived self-efficacy of an individual can be seen in the sense of achievement emotion, as a cognitive evaluation process for a specific learning and achievement event and confirms the assumption that the use of serious games can affect learners' achievement emotions. The objective of this work is the theoretical analysis of the effects of game-based learning on the learner's achievement emotions and on whether the systematic use of serious games has a positive effect on existing negative mindsets. This research is part of an Horizon 2020 project called NEMESIS. The aim of the project is to combine education, technology and social innovation to sensitize today's youth to the social concerns and create the changemakers of the future. Through the use of the NEMESIS serious game, the expectation of self-efficacy is to be promoted, and awareness of the concerns of the social future and empathy is to be raised. This paper focuses on the theoretical consideration of the connection between serious games and achievement emotions in relation to the didactic conception of the game, in which the active engagement with the topic of social innovation and the emotional experience during the learning process is addressed.<br
Keywords: Games; Game-based Learning; achievement emotions; social innovation; self-efficacy: